1996
DOI: 10.1002/(sici)1096-9136(199602)13:2<125::aid-dia13>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Non-insulin-dependent Diabetes and 11-Year Mortality in Asian Indian and Melanesian Fijians

Abstract: This study reports 11‐year all‐cause and cause‐specific mortality rates according to baseline glucose tolerance for a population‐based sample of adult Melanesian and Indian Fijians (n = 2638), first surveyed in 1980. Risk factors for all‐cause and cardiovascular disease (CVD) mortality in subjects with non‐insulin‐dependent diabetes (NIDDM) are also described. The baseline survey included 75 g oral glucose tolerance tests, measurements of blood pressure, body mass index, and triceps skinfold, assays of plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Dubbo study [42] EPESE [43] Adventist Health Study [39] Reykjavik study [47] Collins et al − Melanesians [41] Kuopio higher in women than in men [37]. Similarly, data from the UK Prospective Diabetes Study indicated that men with newly diagnosed diabetes were significantly less obese compared with newly diagnosed women [35].…”
Section: Nhanes I [46]mentioning
confidence: 99%
“…Dubbo study [42] EPESE [43] Adventist Health Study [39] Reykjavik study [47] Collins et al − Melanesians [41] Kuopio higher in women than in men [37]. Similarly, data from the UK Prospective Diabetes Study indicated that men with newly diagnosed diabetes were significantly less obese compared with newly diagnosed women [35].…”
Section: Nhanes I [46]mentioning
confidence: 99%
“…Hypertension, 6 diabetes mellitus, 52,53 dyslipidemia, 54,55 and atrial fibrillation are the most common known risk factors in stroke etiology. The prevalence of these risk factors is known to differ among various ethnic groups 56 and is also associated with manifestations of different stroke subtypes.…”
Section: Cardiovascular Risk Profilementioning
confidence: 99%
“…75 However, a direct comparison of Indian migrants to rural contemporaries in villages of origin in India showed no differences in the rates of glucose intolerance. 76 Moreover, despite varied lifestyle approaches, cross-sectional studies from Fiji 6 and Tanzania 8 also question whether urbanization has a role to explain the high prevalence of diabetes among Indian populations. Hence, not only is diabetes more common among South Asians compared with other ethnic groups, 77 but it is likely that this is a hereditable risk factor in this population.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…T he increased risk of mortality in diabetic patients compared with that of nondiabetic individuals has been reported in different populations (1)(2)(3)(4)(5)(6)(7)(8). Although some of these studies described sex differences in specific cardiovascular risk factors that may account for differences in cardiovascular mortality (4,6), little attention has been given to the possibility that factors predicting overall mortality could vary between diabetic men and women.…”
mentioning
confidence: 99%